Neuroanatomical Changes Underlying Vertical HIV Infection in Adolescents - Yu, Xiao; Gao, Lei; Wang, Haha; Yin, Zhuang; Fang, Jian; Chen, Jing; Li, Qiang; Xu, Haibo; Gui, Xien (Frontiers in Immunology, 2019)
Purpose: The aim of this study was to investigate how human immunodeficiency virus (HIV) affects cerebral cortex development in adolescent children, what are susceptible brain regions, and how these brain structural changes correlate with cognitive abilities. Methods: We used structural magnetic resonance imaging to examine gray matter volume and cortical thickness in 16 HIV-infected children (mean age = 13.63 years) and 25 HIV-exposed uninfected children (mean age = 13.32 years), 12 of them were subjected to a one-year repetitive magnetic resonance scan of the brain. Five neurocognitive tests were performed on each subject to assess cognitive performance in different areas. Results: Cross-sectional studies showed that the gray matter volume of HIV-infected children was widely reduced (mainly in the bilateral frontal, temporal, and insular regions, and cerebellum). The changes in cortical thickness were mainly due to thinning of the right temporal lobe and thickening of the left occipital lobe. Longitudinal studies showed that the gray matter volume reduction of HIV-infected children after one year mainly occurs in the advanced functional area of the right prefrontal, parietal lobe and the motor area, cortical thinning of brain regions were sensorimotor cortex and the limbic system. The gray matter volume of the bilateral cerebellum was positively correlated with the performance of the Wisconsin Card Sorting Test, while the cortical thickness of the right dorsolateral prefrontal cortex was negatively correlated with this test. Conclusion: This study found that HIV-infected pubertal children showed a delayed cortical maturation with atrophy. This abnormal pattern of cortical development may be the structural basis for cognitive impairment in HIV-infected children.